Brain Activation in Contrasts of Microexpression Following Emotional Contexts - Zhang, Ming; Zhao, Ke; Qu, Fangbing; Li, Kaiyun; Fu, Xiaolan (Frontiers in Neuroscience, 2020)
The recognition of micro-expressions may be influenced by emotional contexts. The micro-expression is recognized poorly when it follows a negative context, in contrast to a neutral context. Based on the behavioral evidence, we predicted that the effect of emotional contexts might be dependent on neural activities. Using the synthesized micro-expressions task modified from the Micro-Expression Training Tool (METT), we performed an fMRI study to compare brain response in contrasts of the same targets following different contexts. Behaviorally, we observed that the accuracies of target micro-expressions following neutral contexts were significantly higher than those following negative or positive contexts. At the neural level, we found increased brain activations in contrasts of the same targets following different contexts, which reflected the discrepancy in the processing of emotional contexts. The increased activations implied that different emotional contexts might differently influence the processing of subsequent target micro-expressions and further suggested interactions between the processing of emotional contexts and of micro-expressions.